Synthesis of functionalized polyisobutylene and its block copolymers with D,L-lactide - Nikishau, Pavel A.; Ksendzov, Evgenii A.; Shiman, Dmitriy I.; Gaponik, Ludmila V.; Kostjuk, Sergei V. (Journal of the Belarusian State University. Chemistry, 2019)
Method of reactive polyisobutylene modification by various alkoxybenzenes (anisole and 4-phenoxybutanol) was proposed to form functionalized polyisobutylenes. Polymerization of D,L-lactide was explored on the 4-phenoxybutanol/1,5,7-triazabicyclo[4.4.0]dec-5-ene system. It led to determination of optimal conditions for gaining of poly(isobutylene-b-D,L-lactide). Such copolymers (Mn = 14 300 g/mol and Mn = 36 600 g/mol, Mw / Mn ≤ 2.5) which were obtained by the polymerization of D,L-lactide on polyisobutylene macroinitiator shows microphase ordering. Formation of the block copolymers is confirmed by 1Н NMR spectroscopy, gel permeation chromatography, and scanning electron microscopy.